Effect of New Catalytic Systems on the Process of Anthracene Hydrogenation - Baikenov, M.I.; Baikenova, G.G.; Isabaev, A.S.; Tateeva, A.B.; Akhmetkarimova, Zh.S.; Tusipkhan, A.; Mataeva, A.Zh.; Esenbaeva, K.K. (ALLERTON PRESS INC, 2014)
The hydrogenation of anthracene in the resence of the nanosized catalysts based on iron β FeOOH and Fe(OA)3 (OA refers to oleic acid) and the spherical catalysts NiO/SiO2 and Fe2O3/SiO2 obtained from ash and slag from thermal power plants was studied. It was found that the above catalytic systems can arranged in the following order according to the yields of hydrogenation and destruction products upon the hydrogenation of polycyclic hydrocarbons: β FeOOH, Fe(OA)3, and Fe3O4 nanoparticles > NiO/SiO2 and Fe2O3/SiO2 spherical catalysts > commercial cobalt–molybdenum catalyst. It was established that the test catalysts are promising for the hydrogenation of polycyclic hydrocarbons, and they can be used for the direct liquefaction of coal.